WHAT UNRELATED HEMATOPOIETIC STEM CELL TRANSPLANTATION IN THALASSEMIA TAUGHT US ABOUT TRANSPLANT IMMUNOGENETICS. - Giorgio La Nasa; Adriana Vacca; Roberto Littera; Eugenia Piras; Sandro Orru; Marianna Greco; Carlo Carcassi; Giovanni Caocci (Mediterranean Journal of Hematology and Infectious Diseases)
Abstract Although the past few decades have shown an improvement in the survival and complication-free survival rates in patients with beta-thalassemia major and gene therapy is already at an advanced stage of experimentation, hematopoietic stem cell transplantation (HSCT) continues to be the only effective and realistic approach to the cure of this chronic non-malignant disease. Historically, human leukocyte antigen (HLA)-matched siblings have been the preferred source of donor cells owing to superior outcomes compared with HSCT from other sources. Nowadays, the availability of an international network of voluntary stem cell donor registries and cordon blood banks has significantly increased the odds of finding a suitable HLA matched donor. Stringent immunogenetic criteria for donor selection have made it possible to achieve overall survival (OS) and thalassemia-free survival (TFS) rates comparable to those of sibling transplants. However, acute and chronic graft-versus-host disease (GVHD) remains the most important complication in unrelated HSCT in thalassemia, leading to considerable rates of morbidity and mortality for a chronic non-malignant disease. A careful immunogenetic assessment of donors and recipients makes it possible to individuate appropriate strategies for its prevention and management. This review provides an overview on recent insights about immunogenetic factors involved in GVHD, which seem to have a potential role in the outcome of transplantation for thalassemia.